2018
DOI: 10.1002/app.47208
|View full text |Cite
|
Sign up to set email alerts
|

Inner relationship between the damping property and the sand‐fixing durability of polymer materials

Abstract: This article for the first time reveals the impact of the damping property of materials on its sand‐fixing durability. Based on the turbulence of wind, it could be regarded as a kind of periodic mechanical force. So, when polymers are used to fix sand, they would constantly perceive a periodic force of wind. And, this force would give rise to yielding fracture and fatigue of polymer, so that the sand‐fixing durability of material could be weakened significantly. To impair the periodic force of wind and extend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…The traditional planting and artificial sand‐fixing measures used for desertification control are relatively slow, while chemical sand‐fixing is attracting increasing attention 20–22 . The polymer curing agents commonly used in chemical sand‐fixing include polyacrylamide (PAM), carboxymethyl cellulose, and other synthetic materials, but most have poor wind or water resistance 23,24 . PAM applied to sand fixation acts as a binding and settling agent to increase the formation of sand aggregates, and the adhesive action of the PAM minimizes the erosion of sand particles caused by wind 25–29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional planting and artificial sand‐fixing measures used for desertification control are relatively slow, while chemical sand‐fixing is attracting increasing attention 20–22 . The polymer curing agents commonly used in chemical sand‐fixing include polyacrylamide (PAM), carboxymethyl cellulose, and other synthetic materials, but most have poor wind or water resistance 23,24 . PAM applied to sand fixation acts as a binding and settling agent to increase the formation of sand aggregates, and the adhesive action of the PAM minimizes the erosion of sand particles caused by wind 25–29 .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] The polymer curing agents commonly used in chemical sand-fixing include polyacrylamide (PAM), carboxymethyl cellulose, and other synthetic materials, but most have poor wind or water resistance. 23,24 PAM applied to sand fixation acts as a binding and settling agent to increase the formation of sand aggregates, and the adhesive action of the PAM minimizes the erosion of sand particles caused by wind. [25][26][27][28][29] Over the past decade, basic research on the polymer curing agent hydroxypropyl methyl cellulose (HPMC) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the development and use of new sand-fixing materials has achieved remarkable results in China and abroad. In recent years, domestic research has mainly focused on chemical sand fixing, such as polymer materials, organic-inorganic composite materials, and modified waste plastic materials [9][10][11][12][13]. International researchers have conducted numerous studies on microbial soil modification [14][15][16], using microbial metabolic activities to induce or control a series of chemical reactions in the soil to improve the soil, thereby achieving sand fixation [17][18][19].…”
Section: Introductionmentioning
confidence: 99%